Association of Dietary Niacin Intake with Diabetes in Adults in the United States - Liu, Chan; Duan, Wenjuan; Xu, Wenming (Experimental and Clinical Endocrinology & Diabetes, 2023)
Objective Previous studies have shown inconsistent associations between niacin supplementation and diabetes, and little is known about the relationship between dietary niacin intake and the risk of diabetes in the general population. Our study aimed to explore the association between dietary niacin intake and the risk of diabetes in the adult population in the United States.Methods Data from the 2005–2016 National Health and Nutrition Examination Surveys were analyzed. Diabetes was diagnosed according to the American Diabetes Association criteria. Multivariate logistic regression models were used to estimate the association between dietary niacin intake and diabetes. Covariates included age, sex, race, family income, educational level, drinking status, smoking status, marital status, and physical activity.Results This study included 24494 participants, of which 13.63% had diabetes. In the fully adjusted model, a high niacin intake was significantly associated with a reduced risk of diabetes in a dose-dependent manner. When extreme quintiles of niacin intake were compared, the multivariable-adjusted odds ratio was 0.66 (95% confidence interval: 0.49, 0.88) for diabetes, and per ten-unit increment in dietary niacin intake was associated with a 14% lower risk of diabetes. When niacin intake was less than 15.01 mg/d, a ten-unit increment in niacin intake was associated with a 24% higher risk of diabetes. However, the effect was not statistically significant.Conclusions Our results suggest that the consumption of adequate amounts of niacin can reduce the risk of diabetes. Furthermore, this protective effect disappeared when the niacin intake was insufficient (less than 15.01 mg/d).
Keywords: dietary intake; niacin; diabetes; United States